Prevalence of Diabetic Nephropathy among Type 2 Diabetes Mellitus Patients in Mukalla City, Yemen - Abdulaziz S. Bamahel (Enhanced Knowledge in Sciences and Technology, 2022)
Diabetic nephropathy is one of the most serious complication of diabetes mellitus, which is clinical syndrome characterized by relentless albuminuria leading cause of kidney failure and subsequent dialysis, and it’s major cause of premature death in patients with diabetes: In Mukalla City-Yemen there is no previous published studies about prevalence of diabetic nephropathy among type 2 diabetic patient, The study aimed to determine the prevalence of diabetic nephropathy and risk factor among type 2 diabetic patients in Mukalla city, Yemen. A cross sectional study conducted among 127 medically diagnosed patients with type 2 DM, in five health centers which provide health care for diabetic mellitus patients in Mukalla city, Yemen during (1 March to 30 April 2020). Data was collecting by interview (face to face) by using questionnaire and laboratory investigation (microalbuminuria test and serum creatinine test). We found that 43 of patients had diabetic nephropathy giving prevalence (33.9 %). The results show there was statistical significant association between diabetic nephropathy, duration of DM and hypertension, while there is no statistical significant association between diabetic nephropathy, age and gender, and the level of serum creatinine in all type 2 DM patients was normal, the prevalence of diabetic nephropathy among type 2 DM patients was high, and microalbuminuria test was more reliable for detecting early stages of diabetic nephropathy than serum creatinine.